2018
DOI: 10.1002/mbo3.766
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a bivalent protein as a vaccine against Edwardsiella anguillarum and Vibrio vulnificus in Japanese eel (Anguilla japonica)

Abstract: The OMPs A (OmpA)—of Edwardsiella anguillarum and OmpU of V. vulnificus have been proven to be good antigens. In this study, after construction of a vector, a new recombinant Omp (rOMP) containing both OmpA and OmpU was expressed and purified. Then, the Japanese eels ( Anguilla japonica ) were intraperitoneally (i.p.) injected with the phosphate‐buffered saline (PBS group), formalin‐killed‐cell (FKC group) or the recombinant Omp (rOMP group).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…At present, it is believed that the pathogenesis of V. vulnificus infection mainly depends on the synergistic effect of multiple virulence factor genes. In addition to the well-defined main virulence genes vvhA and rtxA , other virulence genes, such as Wza (capsular polysaccharide outer membrane protein) and OmpU (conserved outer membrane porin), are thought to play a role in the pathogenic process of V. vulnificus [ 28 ]. Wza plays an important role in protecting bacteria from the host’s innate immune response and is widespread among pathogenic Vibrio spp.…”
Section: Methodsmentioning
confidence: 99%
“…At present, it is believed that the pathogenesis of V. vulnificus infection mainly depends on the synergistic effect of multiple virulence factor genes. In addition to the well-defined main virulence genes vvhA and rtxA , other virulence genes, such as Wza (capsular polysaccharide outer membrane protein) and OmpU (conserved outer membrane porin), are thought to play a role in the pathogenic process of V. vulnificus [ 28 ]. Wza plays an important role in protecting bacteria from the host’s innate immune response and is widespread among pathogenic Vibrio spp.…”
Section: Methodsmentioning
confidence: 99%
“…Other outer membrane proteins (Omp)‐based vaccines have been developed, the most used being OmpU, OmpA and OmpII from V. vulnificus , E. anguillarum and A. hydrophila , respectively (Table 5). After vaccination and challenge with a given pathogen, eels vaccinated with Omp generally had significantly higher relative survival than those vaccinated with control solution (Guo et al., 2019, 2020; He et al., 2020; Le et al., 2018; LiHua et al., 2019).…”
Section: Potential Treatmentmentioning
confidence: 99%
“…However, the treatment did not appear to be effective for A. anguilla (Knopf & Lucius, 2008). While most vaccines are developed to protect against a single pathogen, promising bivalent (Guan et al., 2011; Guo et al., 2019) and trivalent (Zhao et al., 2020) vaccines are also being developed and could protect against different pathogens.…”
Section: Potential Treatmentmentioning
confidence: 99%
“…Due to the good immunogenicity and immune protective effect, outer membrane proteins (Omps) on the surface of Gram-negative pathogenic bacteria have gradually become a research hot spot in the development of fish vaccines (Guo, Feng, Lin, Cao, & Zhao, 2015a;Guo et al, 2019;Guo, Lu, et al, 2015;Guo, Wang, Guan, Feng, & Lu, 2013;. It was reported that a single Omp from V. vulnificus, E. anguillarum and A. hydrophila had protective effects in mice, Labeo rohita, Japanese eel and American eel (Duan et al, 2019;He et al, 2018;Yadav, Sahoo, & Dixit, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a single Omp from V. vulnificus, E. anguillarum and A. hydrophila had protective effects in mice, Labeo rohita, Japanese eel and American eel (Duan et al, 2019;He et al, 2018;Yadav, Sahoo, & Dixit, 2014). In recent years, researchers have used the fusion PCR technology to construct a double expression vector of Omp genes and studied the immunogenicity of bivalent expressed Omp, and the results of their studies indicated good immunogenicity and effective protection after the immunization with different bivalent Omps in eels (Guo, Feng, et al, 2015;Guo et al, 2013Guo et al, , 2019Guo, Lu, et al, 2015). However, these bivalent Omps could not effectively protect against infection by these three pathogens simultaneously.…”
Section: Introductionmentioning
confidence: 99%